'Cool Japan': Anime, soft power and Hong Kong generation Y travel to Japan. Issue 2 (3rd April 2019) - Agyeiwaah, Elizabeth; Suntikul, Wantanee; Carmen, Li Yee Shan
ABSTRACT: The 'Cool Japan' strategy was launched in 2012 as a 'soft-power' initiative to promote the unique culture of Japan. Tourism motivated by Japanese animation, or anime, plays an important role in this campaign. While this aspect of Japanese popular culture has been a particular element of attraction, especially for youth travelers, little is known empirically about the degree to which it actually motivates desire to travel to Japan. This paper examines the influence of anime on Hong Kong Generation Y travel to Japan. Based on a quantitative approach, respondents were divided into four clusters – enthusiastic, interested, low viewers, and indifferent – distinguished by varying degrees of interest in anime and corresponding travel motivation. This study contributes to the existing literature by elucidating how anime serves as a travel motivator, proposing a conceptual framing of the relation between anime consumption and travel to Japan in terms of 'soft power, ' the application of cultural ideas and artifacts to encourage positive associations with a country and its values. The findings have implications for destination marketing organization in developing anime products and events that meet the unique needs and preferences of different groups of anime fans, constituting different potential tourism subniches.